Chromium-modified montmorillonite dispersions in stabiblizing derma collagen structure - Паламар, Віра Анатоліївна; Марухленко, Марія Олександрівна; Мокроусова, Олена Романівна (Eastern-European Journal of Enterprise Technologies, 2015)
We have studied how chromium-modified montmorillonite dispersions impact the stabilization of derma collagen structure and registered a high rate of absorbing chromium-based compounds. Chromium-modified montmorillonite dispersions used in tannage would reduce the share of chromium oxide in the exhaust ooze by 30.0 %. Since montmorillonite has a highly adsorbing surface, it increases the efficiency of chromium-based compounds absorption. As a result derma acquires additional active centers for fixing chromium-based compounds, which increases the share of bound chromium oxide in derma and raises the leather welding temperature. The experimental leather has high physical and mechanical characteristics. Owing to montmorillonite dispersion, the leather lengthens by 1.5-7.0 % less and becomes softer. The findings of chemical analysis show that the experimental leather contains more mineral substances, and this index in test samples does not exceed 5.0 %. Chromium-modified montmorillonite dispersions used in tanning hides would extend the leather output piece by up to 4.7 %, raise the leather thickness by 3.5 %, and increase its output volume by 18.0 %. An optimal tanning would reduce the consumption of chromium-based tanning agents by 16.0 %.